PENGARUH KECUKUPAN MODAL DANA PIHAK KETIGA DAN RISIKO KREDIT TERHADAP PROFITABILITAS PADA BANK MUAMALAT INDONESIA TAHUN 2013-2022 - gustira, fira; Mubyarto, Novi; Putra, Darma (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research is to analyze whether there is an influence of capital adequacy of third party funds and credit risk on profitability at Bank Muamalat Indonesia in 2013-2022. This type of research is quantitative using multiple linear regression data analysis techniques and this research uses secondary data. The results of this research show that capital adequacy partially has a negative and significant effect on profitability at Bank Muamalat in 2013-2022, Third Party Funds partially has a negative and significant effect on profitability at Bank Muamalat in 2013-2022, Credit Risk partially has a negative and significant effect on profitability at Bank Muamalat in 2013-2022, capital adequacy, third party funds and credit risk simultaneously have a positive and significant effect on profitability at Bank Muamalat in 2013-2022.